Association of accumulated advanced glycation end‐products with a high prevalence of sarcopenia and dynapenia in patients with type 2 diabetes. Issue 5 (19th February 2019) - Mori, Hiroyasu; Kuroda, Akio; Ishizu, Masashi; Ohishi, Mami; Takashi, Yuichi; Otsuka, Yinhua; Taniguchi, Satoshi; Tamaki, Motoyuki; Kurahashi, Kiyoe; Yoshida, Sumiko; Endo, Itsuro; Aihara, Ken‐ichi; et al.
Abstract: Aims/Introduction: Advanced glycation end‐products (AGEs), which are a major cause of diabetic vascular complications, accumulate in various tissues under chronic hyperglycemic conditions, as well as with aging in patients with diabetes. The loss of muscle mass and strength, so‐called sarcopenia and dynapenia, has recently been recognized as a diabetic complication. However, the influence of accumulated AGEs on muscle mass and strength remains unclear. The present study aimed to evaluate the association of sarcopenia and dynapenia with accumulated AGEs in patients with type 2 diabetes. Materials and Methods: We recruited 166 patients with type 2 diabetes aged ≥30 years (mean age 63.2 ± 12.3 years; body mass index 26.3 ± 4.9 kg/m 2 ; glycated hemoglobin 7.1 ± 1.1%). Skin autofluorescence as a marker of AGEs, limb skeletal muscle mass index, grip strength, knee extension strength and gait speed were assessed. Results: Sarcopenia and dynapenia were observed in 7.2 and 13.9% of participants, respectively. Skin autofluorescence was significantly higher in patients with sarcopenia and dynapenia. Skin autofluorescence was the independent determinant for skeletal muscle mass index, grip strength, knee extension strength, sarcopenia and dynapenia. Conclusions: Accumulated AGEs could contribute to reduced muscle mass and strength, leading to sarcopenia and dynapenia in patients with type 2 diabetes. Abstract : The prevalence rates of sarcopenia and dynapenia were 7.2 and 13.9%, respectively, which seemed to be higher than those of non‐diabetic subjects in previous report from Japan. Interestingly, skin autofluorescence (AF) was significantly higher in patients with sarcopenia and dynapenia than patients without those. Skin AF was the independent determinant for sarcopenia and dynapenia.